2015
DOI: 10.1523/jneurosci.0826-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Readers of Lysine Acetylation Regulate Cocaine-Induced Plasticity

Abstract: Epigenetic processes that regulate histone acetylation play an essential role in behavioral and molecular responses to cocaine. To date, however, only a small fraction of the mechanisms involved in the addiction-associated acetylome have been investigated. Members of the bromodomain and extraterminal (BET) family of epigenetic "reader" proteins (BRD2, BRD3, BRD4, and BRDT) bind acetylated histones and serve as a scaffold for the recruitment of macromolecular complexes to modify chromatin accessibility and tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
61
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 70 publications
8
61
0
Order By: Relevance
“…Recently, JQ1 has been shown to inhibit transcriptional responses that occur during memory formation (56), which might be important for mechanisms implicated in addiction and extinction learning. In addition, JQ1 attenuated the rewarding effect of cocaine in rats by interfering with drug-induced plasticity in the NAc (57). In the cocaine study, JQ1 was administered during the acquisition phase of conditioned place preference (57).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, JQ1 has been shown to inhibit transcriptional responses that occur during memory formation (56), which might be important for mechanisms implicated in addiction and extinction learning. In addition, JQ1 attenuated the rewarding effect of cocaine in rats by interfering with drug-induced plasticity in the NAc (57). In the cocaine study, JQ1 was administered during the acquisition phase of conditioned place preference (57).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, JQ1 attenuated the rewarding effect of cocaine in rats by interfering with drug-induced plasticity in the NAc (57). In the cocaine study, JQ1 was administered during the acquisition phase of conditioned place preference (57). Here, we show that bromodomain inhibitors effectively decrease drug self-administration behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data also suggest an underlying role of chromatin remodeling factors in the neurobiology of drug abuse. For example, chronic cocaine exposure results in increased expression of the bromodomain and extraterminal protein BRD4, an epigenetic reader protein (41), and PSMC5, an ATPase-containing subunit of the 19s proteasomal complex (42). We recently demonstrated that an accessory ATPase subunit of the ISWI family of chromatin remodeling complexes, bromodomain adjacent to zinc finger domain 1B, is also upregulated in the NAc (22).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, to the best of our knowledge, there is no publication reporting BET functions specifically in retinal degeneration. Two recent brain studies identified BET4-mediated transcriptional activation during memory formation [31] and cocaine-induced neuronal plasticity [32]. Another relevant study showed an inhibitory effect of JQ1 on human umbilical vein endothelial cell proliferation, migration, and tube formation [33].…”
Section: Discussionmentioning
confidence: 99%